2017
DOI: 10.1152/physiol.00038.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Interferon Regulatory Factor Signaling in Cardiometabolic Diseases

Abstract: Interferon regulatory factors (IRFs) are evolutionarily conserved proteins expressed not only in immune cells but also in other tissues and organs outside the immune system. In this review, we discuss mechanisms responsible for IRF-mediated innate immune responses and the function and mechanism of IRFs in cardiometabolic diseases. We focus on the role of IRFs in innate immunity and cardiometabolic homeostasis, and highlight reprogrammed IRF signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 126 publications
(143 reference statements)
1
17
0
Order By: Relevance
“…In hepatocytes, PRR‐elicited intracellular signaling can activate or coregulate the transcription of nuclear transcription factors (IRF, NF‐κB, peroxisome proliferator‐activated receptor [PPAR]‐α, stearoyl‐CoA desaturase‐1, etc.) and modulate intrahepatic inflammation and broad metabolic profiles …”
Section: Parenchymal Cells Of the Liver With Immune Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocytes, PRR‐elicited intracellular signaling can activate or coregulate the transcription of nuclear transcription factors (IRF, NF‐κB, peroxisome proliferator‐activated receptor [PPAR]‐α, stearoyl‐CoA desaturase‐1, etc.) and modulate intrahepatic inflammation and broad metabolic profiles …”
Section: Parenchymal Cells Of the Liver With Immune Functionsmentioning
confidence: 99%
“…and modulate intrahepatic inflammation and broad metabolic profiles. (51)(52)(53)(66)(67)(68)(69)(70) Eicosanoids, such as prostaglandins (PGs), thromboxanes (TXs), and leukotrienes (LTs), are wellknown mediators of inflammation responses. (71) Cyclooxegenase (COX) is a critical enzyme in the pathway that leads to formation of PGs and TXs from arachidonic acid (AA).…”
Section: Hepatocytesmentioning
confidence: 99%
“…[120] TRAF1 and TRAF6 can be utilized to promote the activation of ASK1 whereas deubiquitinase TNFa-induced protein 3 (TNFAIP3), dickkopf-3 (DKK3), CASP8 and FADD-like apoptosis regulator (CFLAR), cellular repressor of E1A-stimulated genes (CREG) and caspase recruitment domain 6 can suppress ASK1 activation, which improves the NASH. [111,115,[134][135][136] Different types of IRFs play various roles. Cylindromatosis (CYLD), ubiquitin-specific protease 18 (USP18), and dual-specificity phosphatase 14 (DUSP14) are reported to be candidate enzymes for suppressing the progression of NASH via inhibiting TAK1, [92,[128][129][130] whereas the E3 ligase tripartite motif 8, TRAF3, promotes NASH.…”
Section: Inflammation and Innate Immunitymentioning
confidence: 99%
“…The increased production of endothelin-1 (ET-1), Ang II, catecholamines and pro-inflammatory cytokines activate their cognate receptors and downstream signaling events, which lead to cardiomyocytes necrosis, apoptosis, autophagy, or hypertrophy; and promote fibroblast activation to produce collagen and other proteins that cause fibrosis [35-37]. Recently, we and others have shown that H 2 can prevent various heart diseases through blocking parts of these molecular and cellular signaling events described above (Table 2).…”
Section: The Effects Of H2 In Heart Diseasesmentioning
confidence: 99%